2005
DOI: 10.1093/ndt/gfh893
|View full text |Cite
|
Sign up to set email alerts
|

Severe syncope and sudden death in children with inborn salt-losing hypokalaemic tubulopathies

Abstract: In conclusion, severe chronic or acute hypokalaemia is hazardous in inborn salt-losing tubulopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…They also found that his ECG showed a prolonged QT interval as found in our patient. Similarly, severe syncope of a child with GS who had severe ventricular arrhythmia has been reported by Cortesi et al [17]. Thus detailed investigation into ventricular arrhythmia, particularly in patients with the prolonged QT interval, is warranted.…”
Section: Discussionsupporting
confidence: 52%
“…They also found that his ECG showed a prolonged QT interval as found in our patient. Similarly, severe syncope of a child with GS who had severe ventricular arrhythmia has been reported by Cortesi et al [17]. Thus detailed investigation into ventricular arrhythmia, particularly in patients with the prolonged QT interval, is warranted.…”
Section: Discussionsupporting
confidence: 52%
“…In Gitelman syndrome and in the various forms of Bartter syndrome intercurrent illnesses or discontinuation of regular medication sometimes exacerbate hypokalemia and therefore may cause severe cardiac arrhythmias [23]. The present observations indicate that congenital renal tubular disorders predispose to hypokalemic rhabdomyolysis as well.…”
Section: Discussionmentioning
confidence: 57%
“…Malignant arrhythmias and acute dehydration are the main reasons. However, at the last examination, when the baby was aged 6 months, electrolyte levels were normal (Table 1) and no intercurrent severe acute dehydration was reported [17].…”
Section: Discussionmentioning
confidence: 96%